Pendekatan TPACK Berbasis Media Digital dan Strategi Deep Learning dalam Pembelajaran Bahasa Indonesia pada Materi Gagasan Utama Kelas V SDN Sumberlaseh 1 - Nurul Hidayah; Nurul Kholifah; Nurkhana Aliyah; Nia Rohmatul Fadhilah; Choirin Nisa; Ekawati Fatimatuz Zahro; Siti Hanifatul Hidayah; Siti Badrotul Maghfiroh; Siti Ramadhani; Khoirin Nashiroh; Mohammad Romadhon Habibullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' ability to identify the main idea through the implementation of the Technological Pedagogical Content Knowledge (TPACK) approach based on digital media, integrated with a deep learning strategy. The research was conducted in two cycles consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 20 fifth-grade students at SDN Sumbertlaseh 1 in Bojonegoro Regency. Data collection techniques included tests and observations. The test was administered in three stages: pretest, posttest cycle I, and posttest cycle II, using 20 multiple-choice questions based on Indonesian language competence indicators. The results showed an increase in the average score from 3.25 (pretest), to 11.05 (posttest I), and increased further to 17.20 (posttest II). Classical completeness improved from 0% to 5%, and exceeded 70% by the end of the second cycle. These results demonstrate that the TPACK approach combined with deep learning strategies is effective in enhancing students’ understanding of main ideas in reading texts.